ChemInform Abstract: Tidbits for the Synthesis of Bis(2‐sulfanylethyl)amido (SEA) Polystyrene Resin, SEA Peptides and Peptide Thioesters. Issue 14 (8th April 2014) - Ollivier, Nathalie; Raibaut, Laurent; Blanpain, Annick; Desmet, Remi; Dheur, Julien; Mhidia, Reda; Boll, Emmanuelle; Drobecq, Herve; Pira, Silvain L.; Melnyk, Oleg
Abstract Review: 47 refs.